2000
DOI: 10.1029/2000jd900043
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the effect of clouds on the arctic surface energy budget

Abstract: Abstract. The relationship between cloudiness and sea ice thickness over the Arctic Ocean is examined using an idealized equilibrium energy budget model and a singlecolumn model (SCM) forced by incoming solar radiation, atmospheric poleward energy flux, oceanic heat flux, and sea ice divergence. The sensitivity of ice thickness to cloud perturbations in the SCM is qualitatively different from previous modeling studies, which did not allow the atmospheric temperature profile to respond to perturbations in cloud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…This points out on the importance of clouds and air moisture. The difference in downward longwave radiation between overcast and clear skies is typically 70–100 W/m 2 [ Beesley , 2000; Intrieri et al , 2002; Wang and Key , 2005]. It is, however, not only the cloud fraction and thickness that control longwave radiation, but also the phase of clouds; water clouds have a significantly higher longwave emissivity than ice clouds [ Wang and Key , 2005; Pinto et al , 1997].…”
Section: Discussionmentioning
confidence: 99%
“…This points out on the importance of clouds and air moisture. The difference in downward longwave radiation between overcast and clear skies is typically 70–100 W/m 2 [ Beesley , 2000; Intrieri et al , 2002; Wang and Key , 2005]. It is, however, not only the cloud fraction and thickness that control longwave radiation, but also the phase of clouds; water clouds have a significantly higher longwave emissivity than ice clouds [ Wang and Key , 2005; Pinto et al , 1997].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in Arctic cloudiness can have discernible effects on the surface energy budget (Wang and Key, 2003;Beesley, 2000;Kay et al, 2008Kay et al, , 2012. Lower level Arctic stratiform clouds are regarded as an especially important target for improved numerical simulations (Smith and Kao, 1996;Harrington et al, 2000;Francis and Hunter, 2007;Fridlind et al, 2007;Klein et al, 2009;Morrison et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…While limited to thinner clouds, this approach is appealing because, from a climatological standpoint, it is downwelling thermal emission that plays a dominant role in the Arctic surface radiation balance (Beesley, 2000;Francis and Hunter, 2006). Retrievals are based on the part of the electromagnetic spectrum that is coupled to the physics in question.…”
Section: Introductionmentioning
confidence: 99%
“… Curry et al [1993] conducted sensitivity studies in which they varied the properties of clouds and found that the mean thickness of Arctic sea ice was very sensitive to cloud characteristics. Beesley [2000] also examined the relationship between clouds and Arctic ice thickness using an energy budget and a single column model in which he incorporated thermodynamic coupling of the atmosphere and surface. He showed this coupling was essential and that local feedbacks can affect the dependence of ice thickness on cloud perturbations.…”
Section: Introductionmentioning
confidence: 99%